The Effect of Green-Technology Application on Financial Performance of Accredited Hospitality Facilities in Kenya - Nyamogosa, Henry Mogaka; Obonyo, George Otieno; Chepngetich, Beatrice (Journal of Modern Hospitality, 2025)
Purpose: The study investigated the effect of green-technology application on financial performance of accredited hospitality facilities in Kenya. The study particularly examined the effect of energy-efficient appliances, water-efficient appliances and waste management appliances on financial performance of accredited hospitality facilities in Kenya. Methodology: Anchored on resource-based view and Porter’s Competitive Advantage theories, a quantitative approach with a cross-sectional survey research design was used to collect and analyze data. A sample size of 216 respondents from 449 targeted hospitality facility managers was obtained via stratification and proportionate sampling technique. Findings: The findings revealed that green-technology application has a significant positive effect on financial performance of accredited hospitality facilities. The energy-efficient appliances had the strongest effect (β = .354, t = 5.73, p < .001) on financial performance of accredited hospitality facilities, followed by waste management appliances (β = .315, t = 5.17, p < .001) and water-efficient appliances (β = .230, t = 3.81, p < .001). Unique Contribution to Theory, Policy and Practice: The study isolates the relative financial effect of water-efficient, energy-efficient and waste management appliances empirically, hence advancing the Resource-Based View and Porter’s Competitive Advantage. This establishes a hierarchy of strategic value among green technologies in hospitality facilities. Also, the study gives evidence-based justifications for government agencies and regulators to incentivize energy-efficient technologies, embrace public-private partnerships for training, encourage sustainability standards and align hospitality operations with national sustainability goals. Hospitality managers get actionable guidance from the study to prioritize energy-efficient appliances for immediate financial benefits while integrating water and waste management technologies as a strategic lever for long-term financial performance and competitiveness.